Modular custom prosthetic reconstruction of proximal tibia giant cell tumor: a case report and review of literature - Gupta, Vatsal A.; Tomar, Aman; Katkani, Anmol; Modi, Lomesh; Desai , Sarvang M. (International Journal of Research in Orthopaedics, 2025)
Giant cell tumors (GCTs) of bone are primary bone tumors that are benign in nature. They are biologically aggressive and have metastatic potential after malignant transformation. They occur in skeletally mature individual mainly in 3rd decade of life. Here, we present a case of a 29-year-old female diagnosed with right proximal tibia GCT, managed with en bloc excision and custom mega prosthesis arthroplasty.